PENERAPAN MODEL PEMBELAJARAN COOPERATIVE PICTURE AND PICTURE UNTUK MENINGKATKAN HASIL BELAJAR IPA MATERI SISTEM REPRODUKSI MANUSIA PADA SISWA KELAS 9H DI SMP NEGERI 10 JEMBER - Soesy Sri Wulandari; Suwoto Suwoto (Jurusan Pendidikan MIPA FKIP Universitas Jember, 2019)
Abstract: The purpose of this study is to improve the learning outcomes of IPA students in class 9 H in SMP Negeri 10 Jember with picture and picture model). The type of research is Class Action Research (CAR). Class action in this research is done with two cycles. Each cycle implemented improvements to be achieved through the reflection. The results show that the application of cooperative learning model of picture and picture type can improve the learning outcomes of 9H class students. Cycle 1 achievement Minimum Completion Criteria is 41, 67%, while in Cycle 2 is 83%. Keyword: Picture and Picture Model, IPA Learning Outcomes, Reproduction System